Demographic, nutritional, social and environmental predictors of learning skills and depression in 20,000 Indian adolescents: Findings from the UDAYA survey - Scott, Samuel P.; Pant, Anjali; Nguyen, Phuong Hong; Shinde, Sachin; Menon, Purnima (Public Library of Science, 2020)
Adolescent wellbeing is critical to breaking the intergenerational cycle of poverty and one in five of the world’s adolescents live in India. We explored predictors of learning skills and depression in Indian adolescents.